Degree of Conversion and Oxygen-Inhibited Layer Effect of Three Dental Adhesives - Lindsay Robertson; Melissa Phaneuf; Asmaa Haimeur; Igor Pesun; Rodrigo França (MDPI AG, 2016)
This study investigated the effect of the oxygen-inhibited layer on the degree of conversion (DC) of three dental adhesives, comparing two different protocols. Quartz-tungsten-halogen (QTH) light curing and light-emitting diode (LED) were used to cure three adhesives: OptiBond All in One (OAIO), Adper Easy Bond (AEB) and ExciteF (EXF). The DC was calculated utilizing Fourier Transform infrared spectroscopy (FTIR) (n = 12). The two protocols used were as follows: (i) prevent the oxygen-inhibited layer using a Mylar plastic strip pushed onto each bonding adhesive; and (ii) polymerize samples without a plastic strip. The data was analyzed statistically by a three-way ANOVA, and Tukey Test (a = 0.05). The presence of an oxygen-inhibited layer reduced the DC of the adhesives by 64% for EXF, 46% for AEB and 32% for OAIO. This study suggests that there are differences among the oxygen-inhibited layers present for the adhesives tested.